New record and redescription of Microcotyle helotes Sandars, 1944 (Monogenea: Microcotylidae) in Vietnam - Nguyen, Ha Hoang Thi; Nguyen, Ha Van; Nguyen, Manh Hung (Academia Journal of Biology, 2024)
Twenty-seven specimens of the fish species Terapon jarbua and 4 specimens of the fish species Terapon theraps were collected from the Cat Ba Archipelago marine area, and examined for parasite infection. Among these, 4 specimens of T. jarbua and 1 specimen of T. theraps were infected with a total of 42 monogeneans. The intensity of infection ranged from 1 to 16 worms per fish. Four monogenean species were identified, three of which belong to the Protogyrodactylidae: Protogyrodactylus gussevi (14 specimens) and Protogyrodactylus perforatus (12 specimens) were found on T. jarbua, while Protogyrodactylus solidus (1 specimen) was identified on T. theraps. The species Microcotyle helotes (17 specimens) was recorded for the first time in Vietnam, found in two individuals of the new host T. jarbua. Additionally, a redescription of M. helotes was provided.